2017
DOI: 10.1007/s11524-016-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthful Food-and-Beverage Advertising in Subway Stations: Targeted Marketing, Vulnerable Groups, Dietary Intake, and Poor Health

Abstract: Unhealthful food-and-beverage advertising often targets vulnerable groups. The extent of such advertising in subway stations has not been reported and it is not clear how ad placement may relate to subway ridership or community demographics, or what the implications might be for diets and diet-related health in surrounding communities. Riding all subway lines (n = 7) in the Bronx, NY, USA, investigators systematically assessed all print ads (n = 1586) in all stations (n = 68) in 2012. Data about subway ridersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 17 publications
5
64
0
1
Order By: Relevance
“…Often, targeted marketing appears to influence purchasing and consumption patterns effectively. 22,35 The current findings coupled with research demonstrating that areas with higher percentages of food advertisement had increased odds of sugary drink consumption, 12,17,20 obesity, 12 and diabetes, 20 highlights the important role targeted advertising might play in perpetuating poor health and contributing to persistent health-related disparities in NYC neighborhoods. Given the rising national attention around policy proposals to reduce consumption, 36 understanding how sugary drink advertising is placed across neighborhoods can inform community-based and policy efforts that aim to address sugary drink overconsumption.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Often, targeted marketing appears to influence purchasing and consumption patterns effectively. 22,35 The current findings coupled with research demonstrating that areas with higher percentages of food advertisement had increased odds of sugary drink consumption, 12,17,20 obesity, 12 and diabetes, 20 highlights the important role targeted advertising might play in perpetuating poor health and contributing to persistent health-related disparities in NYC neighborhoods. Given the rising national attention around policy proposals to reduce consumption, 36 understanding how sugary drink advertising is placed across neighborhoods can inform community-based and policy efforts that aim to address sugary drink overconsumption.…”
Section: Discussionsupporting
confidence: 55%
“…In Queens, there was a surprising inverse association observed with the percentage of Latino residents, which is the opposite of what previous research has found. 20,33 As there is considerable diversity within Latino communities (e.g., country of origin, years of acculturation, income, and education levels) and where Latinos reside in NYC, 34 further research may provide additional context to these findings. It is also meaningful that although the percentage of white, non-Latino residents was excluded from adjusted analysis owing to issues of multicollinearity, its significant inverse association at the city level and in 3 of 5 boroughs suggests a protective effect in neighborhoods with large white, non-Latino populations.…”
Section: Discussionmentioning
confidence: 99%
“…[31]. In the Bronx; African-American and Spanish-speaking populations are exposed to more processed food commercials and advertisements than white residents[32,33]. Over the next decade, the marketing of sugar-sweetened beverages is expected to increase dramatically worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Promotion of unhealthful items is also a problem within and outside other food sources ( Ohri-Vachaspati et al, 2014 ) and more broadly in patient communities ( Lesser et al, 2013 ). Advertisements for high calorie, low-nutrient foods appear more often in African American and Latino neighborhoods ( Yancey et al, 2009 ), with subway-station ads in particular targeted to neighborhoods with higher poverty, lower high-school graduation rates, higher percentages of Hispanics ( Lucan et al, 2017 ).…”
Section: Unhealthful Provision and Promotionmentioning
confidence: 99%